2008
DOI: 10.1108/00220410810858047
|View full text |Cite
|
Sign up to set email alerts
|

Author‐rated importance of cited references in biology and psychology publications

Abstract: Purpose -The present study aims to investigate how textual features, depth of citation treatment, reasons for citation, and relationships between citers and citees predict author-rated citation importance. Design/methodology/approach -A total of 49 biology and 50 psychology authors assessed the importance, reason for citation, and relationship to the cited author for each cited reference in his or her own recently published empirical article. Participants performed their evaluations on individualized web-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 29 publications
3
44
0
Order By: Relevance
“…Although some later studies (e.g. Hanney et al, 2005) found no significant difference in terms of citation location for citation importance, many studies found that citations located in the Methodology, Results, Discussion, or Conclusion sections may play a more significant or meaningful role than those located in the introductory sections (Bonzi, 1982;Cano, 1989;Tang & Safer, 2008;Voos & Dagaev, 1976).…”
Section: Research Papermentioning
confidence: 99%
See 3 more Smart Citations
“…Although some later studies (e.g. Hanney et al, 2005) found no significant difference in terms of citation location for citation importance, many studies found that citations located in the Methodology, Results, Discussion, or Conclusion sections may play a more significant or meaningful role than those located in the introductory sections (Bonzi, 1982;Cano, 1989;Tang & Safer, 2008;Voos & Dagaev, 1976).…”
Section: Research Papermentioning
confidence: 99%
“…Bonzi (1982) confirmed results from Herlach (1978) and Voos and Dagaev (1976) that multi-citations can be used as a good predictor of importance or relevance to the citing paper. Tang and Safer (2008) found that giving high importance to multi-citations may help improve citationbased rankings. Zhu et al (2015) also found that in-text citation frequency was the best feature to help spot citations that were considered crucial to the authors of a citing paper, and that frequency-weighted citation ranking can outperform traditional citation ranking of top authors, at least in the research field they studied.…”
Section: Research Papermentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of theoretical dialogue between these two groups of researchers has been notably scarce, perhaps in part because of a tendency for the former group to identify as 'cognitive psychologists', and the latter as 'social psychologists' (Manier, 2004;Roediger, 2010). Even though some of the earliest classic empirical work on memory distortion took a social psychological standpoint (e.g., Bartlett, 1932), over time it may be that authors' citation practices have reinforced and exaggerated the separation of theories from these two sub-disciplines (Tang & Safer, 2008).…”
Section: A Tale Of Two Literaturesmentioning
confidence: 99%